2019
DOI: 10.35333/porta.2019.22
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Water Permeability of Ultrasonic Seaming on PU Coated Fabrics

Abstract: Technical textiles take an important place in textile and apparel sector. In technical textiles, ultrasonic seaming method besides conventional seaming methods is one of the alternative methods used in seaming processes of functional textiles. In this study, the effects of ultrasonic seaming method in which needle and thread usage is not needed on waterproofing property of PU coated fabrics in comparison with conventional seaming methods were investigated. Sewn fabrics obtained with different seaming parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…According to the results of the study, the waterproofing property of the ultrasonic seam is found to be higher than that of the conventional seam. Şevkan Macit and Tiber 18 obtained similar results in terms of the waterproofing property in their study, in which they used polyester woven fabrics. Eryürük et al.…”
mentioning
confidence: 55%
See 1 more Smart Citation
“…According to the results of the study, the waterproofing property of the ultrasonic seam is found to be higher than that of the conventional seam. Şevkan Macit and Tiber 18 obtained similar results in terms of the waterproofing property in their study, in which they used polyester woven fabrics. Eryürük et al.…”
mentioning
confidence: 55%
“…Considering the obtained water permeability test results in general, higher water permeability values are generally observed in the ultrasonic seam; it was even observed that some ultrasonic seams, especially with R1 and R3 rollers, have no water penetration from the fabric during the test. There are studies in the literature showing that the water permeability of ultrasonic seaming is higher than that of conventional seaming 17,18 and that there is no water penetration in ultrasonic seaming. 10 However, at some rollers and velocities in the ultrasonic seam, the values are lower than that of sealed adhesive tape (Figure 6).…”
Section: Resultsmentioning
confidence: 99%
“…2.1 Ultrasonic welding in textile and apparel applications When it comes to the textile and apparel industry, the application of ultrasonic welding can have profound applications in the field of technical textiles (Tiber and S ¸evkan Macit, 2019). Particularly, when it comes to protective wear, the use of stitchless technology is highly advisable as it can eliminate the pores caused due to the piercing of the needle through the fabric.…”
Section: Research Background and Gapsmentioning
confidence: 99%
“…Rani et al [17] have stated the joint strength of ultrasonic welding for acrylonitrile butadiene styrene and highdensity polyethylene and found that the welding time and pressure significantly affected the joint strength. Ayse and Bahar [18] investigated the water permeability of ultrasonic seaming on PU-coated fabrics and observed that the waterproofing values decreased with the increase in seaming velocity. Rajput et al [19] have studied the peel strength of ultrasonic welding on polypropylene and investigated that the amplitude had a significant effect on the peel strength and the most influencing variable than hold time and weld time.…”
Section: Introductionmentioning
confidence: 99%